Protocol development: level of preventive action method, considering the preventive environments in construction works - Carpio, Antonio José; González, María de las Nieves; Martínez, Inmaculada; Prieto, María Isabel (Journal of Civil Engineering and Management, 2020)
The techniques for preventing risk have traditionally been analyzed on an individual basis, it being highly complex to apply preventive procedures across the board in construction works. This implies the necessary risk assessment based on the common factors of Safety at Work, Industrial Hygiene, Ergonomics and Psychosociology. This work analyzes and classifies the environments which characterize the building process: absolute (initial), documentary, construction, social and life cycle, and identifies the technical-documentary processes associated with each one. Finally, a new risk assessment method adapted to building works is proposed, called “Level of Preventive Action”, by means of a new mathematical formula which encompasses Safety at Work, Industrial Hygiene, Ergonomic and Psychosociological factors. It is based upon the development of the William T. Fine method, adapting it to construction works, with the incorporation of six parameters to explain the degree of correction. It consolidates and connects environment parameters to determine the preventive action level of the construction work, with the objective of establishing the levels of preventive control required to achieve an optimum prevention situation. The results of comparison between the environments in the implementation of the new risk assessment methodology during the construction process in a real building work are shown.